Hegel’s View of Language as a Critique of Empiricism (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: In this paper, I discuss Hegel’s theory of language as found in several passages of the Phenomenology of Spirit and argue that this view of language can be taken as a critique of Empiricism as traditionally understood in the British Empiricist tradition and as Hegel discusses it in his Encyclopaedia Logic. Hegel’s view of language is that it is a medium that captures the particular and the individual as well as the universal. I argue that such a language is ontologically epistemological and a priori as well as a posteriori. If Empiricism is the view that knowledge depends on sensory/a posteriori experience and given that Hegel criticizes Empiricism for taking only particulars as opposed to general experience as knowledge, I claim that Hegel’s view of language opposes Empiricism in these two fundamental ways. KEYWORDS: Hegel, Empiricism, Language, Universal, A priori